Non-technological innovation : conceptual approaches, impacts and measurement issues - Pereira, Cristina (2012)
There have been increasing efforts to investigate innovation impacts at the firm level. This paper aims to contribute to this endeavour focusing on the non-technological side of innovation, which has been increasingly considered an important, if not crucial, determinant of successful innovation performance. The main objective of this paper is to present a concise literature review on the subject, highlighting three aspects concerning this theme: the main ideas that populate the debate, the perceived impacts and the measurement issues linked to non-technological innovation. Research gaps and opportunities are also explored.